COVID-19 vaccine hesitancy among pregnant women attending public antenatal clinics in Dar es Salaam, Tanzania - Zainab Hassan Yussuph; Fadhlun M. Alwy Al-Beity; Furaha August; Amani Anaeli (Taylor & Francis Group, 2023)
ABSTRACTThe COVID-19 pandemic has claimed over six million lives and caused significant morbidities globally. The development and use of COVID-19 vaccines is a key strategy in ending this. There is a general public hesitancy on vaccine uptake, including pregnant women who are at high risk of severe forms of the disease and death when infected with the virus. To determine the magnitude of hesitancy toward COVID-19 vaccines and the associated factors among pregnant women attending public antenatal clinics in Dar es Salaam‬. This was a cross-sectional analytical study conducted among 896 pregnant women attending antenatal clinics at public health facilities in Dar es Salaam. A structured interviewer-based questionnaire, in an electronic form, was used. The analysis was done by a multivariable linear regression model using STATA 16 to obtain factors associated with vaccine hesitancy, and P < .05 was considered significant. The proportion of pregnant women with vaccine hesitancy was 45%. Hesitancy was higher among unemployed pregnant women (AOR 2.16 (95% CI 1.36-3.42) and the self-employed group (AOR 1.62 (95% CI 1.07-2.44). It was also higher among pregnant women with poor attitudes to COVID-19 vaccines (AOR 2.44 (95% CI 1.75-3.39) and women who had low perceived benefits of the vaccines (AOR 2.57 (95% CI 1.83-3.60). COVID-19 vaccine-targeted interventions should aim at the provision of knowledge on COVID-19 and the COVID-19 vaccine and address poor attitudes and perceptions that pregnant women have on these vaccines.